Preparing Cities for Future Pandemics: Unraveling the Influence of Urban and Housing Variables on COVID-19 Incidence in Santiago de Chile - Kuschel, K.; Carrasco, R.; Idrovo-Aguirre, B.J.; Durán, C.; Contreras-Reyes, J.E. (Multidisciplinary Digital Publishing Institute (MDPI), 2023)
In this study, we analyzed how urban, housing, and socioeconomic variables are related to COVID-19 incidence. As such, we have analyzed these variables along with demographic, education, employment, and COVID-19 data from 32 communes in Santiago de Chile between March and August of 2020, before the release of the vaccines. The results of our Principal Component Analysis (PCA) confirmed that those communes with more economic, social, organizational, and infrastructural resources were overall less affected by COVID-19. As the dimensions affecting COVID-19 are based on structural variables, this study discusses to what extent our cities can be prepared for the next pandemic. Recommendations for local decision-makers in controlling illegal immigration and investing in housing and urban parks are drawn.
Keywords: COVID-19 incidence; Socioeconomic variables; Principal Component Analysis; https://purl.org/pe-repo/ocde/ford#3.03.09